Manual Prosedur Pensijilan Halal Malaysia Sebagai Suatu Aplikasi Memenuhi Keperluan Konsep Halalan Tayyiban: Suatu Analisis - Mustaffa, Khairul Anuwar; Borhan, Joni Tamkin; Mohd Nor, Mohd Roslan (Online Journal of Research in Islamic Studies, 2017)
This article is an attempt to analyze the extent of the procedure laid down in the Manual Procedure of Malaysian Halal Certification (MPPHM) to meet the requirements and comply with the concept of halalan tayyiban practiced among food manufacturers in the food industry. In general, there are four main elements in this manual procedures that meet the requirements of halalan tayyiban practice that needs confirmation of the ingredients source, the need for food safety control practices and quality, the implementation of halal assurance system and control regulations compliance. To ensure that these elements can be strengthened continuously, the scope of the audit should be detailed, halal assurance system and compliance monitoring and enforcement needs to be improved in addition to the implementation of rigorous research to product output in order to ensure the quality and safety of food produced.